An investigation into the relationship between organizational growth and performance - Baker, Paul russell (2006)
This project investigates the relationship between organizational growth and organizational performance, with a particular focus on the Construction Industry in the UK. The key aim of this project was to review the key variables that influence the relationship between growth and organizational performance. Through reviewing academic literature and from my research findings, I make recommendations to Turner & Townsend a Construction and Management Consultancy as to how to implement a performance measurement framework. The objective is to enhance senior managementsÃÂÃÂ¢ÃÂÃÂÃÂÃÂ awareness of negative factors associated with growth, to enable priorities to be adjusted to mitigate them, and in the process gain improved alignment with the companyÃÂÃÂ¢ÃÂÃÂÃÂÃÂs strategic vision. The research was largely undertaken as a case study of Turner & Townsend, as this method is acknowledged by academics as a rich way of understanding detailed issues, and was a worthwhile way of exploring the practical application of existing theory. The primary research was undertaken via semi-structured interviews. Interviewees were grouped into three themes, namely ÃÂÃÂ¢ÃÂÃÂÃÂÃÂInternalÃÂÃÂ¢ÃÂÃÂÃÂÃÂ, ÃÂÃÂ¢ÃÂÃÂÃÂÃÂExternalÃÂÃÂ¢ÃÂÃÂÃÂÃÂ and ÃÂÃÂ¢ÃÂÃÂÃÂÃÂSupplierÃÂÃÂ¢ÃÂÃÂÃÂÃÂ to enable rounded feedback. In addition I issued a questionnaire to staff to establish their perspective on the impact current growth was having on the organisation. The key findings suggest that some senior management priorities do differ at differing stages of a companiesÃÂÃÂ¢ÃÂÃÂÃÂÃÂ life cycle, although human resource and customer satisfaction remain a consistently important priority at all life cycle stages. In addition, business units within an organisation can be in differing life cycle stages simultaneously, and need management to focus on differing priorities accordingly. Data collected suggested that despite financial performance being seen as a byproduct of all other facets of the business and on paper the least important to actively manage, it was in fact by far the most micro managed and controlled aspect of the business, to the detriment of aspects such as human resource and customer satisfaction. The recommendations are for implementation of a balanced scorecard framework which should address the overemphasis on performance measurement of financial aspects and refocus on human resource, business process and customer satisfaction. The research does not seek to overturn existing theory, but adds to the academic body of knowledge when considering the relationship between organizational growth and performance.